(untitled) (International Congress on Economics, Management and Business Studies, 2026)
This article analyzes investment portfolio performance indicators, particularly Sharpe, Treynor, Sortino, Jensen’s Alpha, and Modigliani–Miller indicators, calculated based on a portfolio formed from 15 stocks. Based on the obtained results, scientific conclusions are presented regarding how effective the portfolio is for investors.